ANALISIS PERUBAHAN KURS RUPIAH TERHADAP DOLLAR AMERIKA - Wati, Yeni (Jurnal Kajian Ekonomi, 2014)
The research aims to identify and analyze (1) effect of inflation to the fluctuation of Rupiah exchange rate against US dollar and (2) effect of interest rate to the fluctuation of Rupiah exchange rate against US dollar. Data used in the research are quarterly time series data, namely in period from 1998-II to 2012-.IV. The analysis tools used in this research are multivariate linear regression. The result of this research concluded that the variables of inflation have significant and negative impact to rupiah exchange rate against US dollar. Variable interest rate have significant and positive impact to rupiah exchange rate. Policy implications of the result of this study are Bank Indonesia as monetary authorities need to be careful in raising the BI rate as measures to prevent collapse of the rupiah against USD.Bank Indonesia also needs to pay attention to the inflation rate can affect the growth rate of the economy and the exchange rate in relation to trade with foreign countries.